Different Timing of Adjuvant Low Dose hCG and GnRH Agonist Trigger Protocol, in OHSS High-Risk Patient with Peak E2 Level <4000 pg/mL - Petanovska Kostova, Emilija Zoran; Sotirovska, Velentina; Dimitrov, Gligor; Stojkovska, Snezana; Hadzi Lega, Makjuli; Stojanovska, Daniela; Stamenkovska, Nikoleta; Simjanovska, Liljana; Petanovski, Zoranco (Gynecology Obstetrics & Reproductive Medicine, 2020)
OBJECTIVE: The aim of the study is to compare the live birth rates between 1,500 I.U. of Human chorionic gonadotropin at the time of Gonadotropin-releasing hormone agonist trigger day or 35-36 h later on the oocyte pick-up day, without affecting the risk of significant ovarian hyperstimulation syndrome development in high-risk patients with peak E2 level <4,000 pg/mL STUDY DESIGN: This single-center prospective cohort study encompassed the period from March 2016 to March 2018 year. A total of 216 patients entered for final analysis, underwent a flexible antagonist protocol, intracytoplasmic sperm injection, and embryo transfer on the 3rd or 5th day in autologous cycles. Patients were randomized in one of two groups: Group A- Dual trigger group - 1,500 IU of Human chorionic gonadotropin at the time of Gonadotropin-releasing hormone agonist trigger day and Group B- 1,500 IU of Human chorionic gonadotropin 35-36 h later, on the oocyte pick-up day. To compare the two groups, we used nonparametric and parametric statistical tests. Significant differences were considered all values of p<0.05. RESULTS: There is no significant difference between the two (A vs B) groups according to the average number of retrieved oocytes (13.08 vs 14.41 p=0.08), M II oocytes (10.5 vs 10.95 p=0.46), GV (1.24 vs 1.52 p=0.09, the fertility rate (68.46% vs 64.04% p=0.07). The dual trigger group (A) had a significantly higher live birth rate (62.29% vs 42.37% p<0.05) compared with the Gonadotropin-releasing hormone-a trigger group (B). There were no cases of moderate or severe ovarian hyperstimulation syndrome in both groups. CONCLUSION: Our study shows that in hyper responders where the E2 peak is <4,000 pg/mL, the two approaches to the final oocyte maturation trigger have a correct outcome of the results, both in terms of the results from the in vitro fertilization and the low risk of ovarian hyperstimulation syndrome appearance.